LABORATORY DIAGNOSIS OF THE LIPID SPECTRUM IN MIGRAINE AND ITS RELATIONSHIP WITH CLINICAL CHARACTERISTICS - Kambarova, Dildora; Usmanova, Durdona (Medical science of Uzbekistan, 2023)
This article discusses changes in the lipid spectrum in patients with migraine. Identified dyslipidemia is considered as a risk factor for vascular complications, regardless of the clinical characteristics of migraine. Elevated HDL levels may play a protective role against vascular complications.